(untitled) (The Macau Ricci Institute Journal, 2023)
What follows is a precis of a larger work that invites us to consider how institutions can be instruments of peace following on from what contemplatives must teach peacemakers. In 2022 the world continues to face a pandemic during the roll out of the United Nations 2030 Agenda for Sustainable Development and China’s Belt and Road Initiative 2049. History has taught us that geographical peace promotion supersedes ideology; the Silk Road attests to that. Peace becomes a matter of survival. The intended audience for this paper is general readers interested in peacemaking. The challenge is for all of us to continue to process what went before, in order to change the future. The infrastructure requires analysis and evaluation and that means, East and West must continue to communicate in specific global ways for an ongoing and effective peace process.